Strategi Promosi Kelompok Bimbingan Ibadah Haji dan Umroh (KBIHU) Al-Kamiliyyah dalam Meningkatkan Jumlah Calon Jamaah Haji - Maulana, Muhammad Agus; Sanusi, Irfan; Rustandi, Ridwan (Tadbir: Jurnal Manajemen Dakwah, 2022)
This study aims to determine how the planning, promotion excellence and implementation of the planning compiled by KBIHU Al-Kamiliyyah in conveying information to the public through the promotional strategies implemented, so as to achieve the target in increasing the number of prospective pilgrims. This research is in accordance with the theory discussed, namely the strategy theory from Buzzer and the promotion mix theory from Philip Khotler whose basic assumptions are that satisfaction and trust depend on the communication tools used and the strategies applied at the time of promotion. This research uses descriptive-qualitative research methods. Data collection was carried out through observation and in-depth interviews with KBIHU Al-Kamiliyyah. The results of the research data show that from the current development of marketing in society, the right promotion to be applied by KBIHU Al-Kamiliyyah in increasing the number of prospective pilgrims is through personal selling with the help of communication tools such as sales presentations, sales meetings, intensive programs and samples of salespeople (retail selling, field selling, executive selling). The implication is that there is a mutually beneficial relationship between the KBIHU Al-Kamiliyyah institution and the community for trust and service satisfaction in implementing implementation.